Exploring the direct and indirect effects of emotional intelligence and frequency of customer contact on organisational citizenship behaviours among hotel employees in Mexico. (2018) - Santos, Angeli; Mustafa, Michael; Cantu, Ana Ayala
In the hotel industry, organisational effectiveness and service quality are highly dependent on front-of-house employees' positive interactions with customers, and their willingness to engage in organisational citizenship behaviours (OCB). Various studies have identified the ability of employees to manage their own emotions and those of others as a key means of understanding how and why employees engage in OCB. The present study seeks to shed light on how the underlying mechanisms of emotional intelligence (EI) and the nature of job role, through the frequency of interactions with customers could be of benefit to service orientated organisations. Empirical evidence was drawn from a sample of 179 front-of-house employees from a four-star Mexican hotel chain. A series of multiple hierarchical regressions revealed that when employees experience high levels of customer contact and engage in high levels of emotion regulation this can have a detrimental effect on their OCB. The findings underscore the importance of the role of work and job context in influencing the EI and OCB relationship.